1997
DOI: 10.1007/bf00942044
|View full text |Cite
|
Sign up to set email alerts
|

p53 protein expression but not mdm-2 protein expression is associated with rapid tumor cell proliferation and prognosis in renal cell carcinoma

Abstract: The clinical course of renal cell carcinoma (RCC) is highly variable. Overexpression of the p53 protein has been suggested as a possible prognostic parameter in RCC. Overexpression of the mdm-2 oncogene product has been shown to interact with the p53 function. To investigate the immunohistochemical overexpression of mdm-2 protein in comparison with that of p53 protein in RCC, 50 nonpapillary pT3 RCCs were immunostained for p53 protein (DO-7) and mdm-2 (IF2). Tumor growth fraction (Ki-67 labeling index; MIB-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 28 publications
(29 reference statements)
7
21
3
Order By: Relevance
“…Mutant p53 forms are detectable by immunohistochemistry due to its extended half-life. Mutant p53 expression is found in 20% to 50% of renal tumors and varies by histologic subtype (27,42,43). Our study confirms that higher p53 protein staining is associated with poor prognosis (27,42,44).…”
Section: Resultssupporting
confidence: 78%
“…Mutant p53 forms are detectable by immunohistochemistry due to its extended half-life. Mutant p53 expression is found in 20% to 50% of renal tumors and varies by histologic subtype (27,42,43). Our study confirms that higher p53 protein staining is associated with poor prognosis (27,42,44).…”
Section: Resultssupporting
confidence: 78%
“…They also observed, similar to our study, an association between P53 and Ki-67 expression. On the other hand, Moch et al reported that Ki-67 expression appeared to be related to survival; however, when evaluated using a multivariate model, only the influence of P53 and stage remained significant [37].…”
Section: Discussionmentioning
confidence: 93%
“…The relationship of leiomyomatous renal cell carcinoma and clear cell papillary renal cancer based on the presence or absence of VHL mutation and/or 3p losses is currently controversial. Apart from the VHL inactivation as an initiating event in clear cell renal cancer, many different genetic alterations have been reported for this tumor type, some of them associated with prognosis [55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Cytogenetic and Molecular Alterations In Renal Cell Carcinommentioning
confidence: 99%